Efek Penambahan Natrium Diklofenak Topikal pada Terapi Injeksi Intravitreal Bevacizumab terhadap Perubahan Visus dan Tekanan Intraokular Pasien dengan Edema Makula Diabetika - Supanji Supanji; Widya Ramania; Melvina Nidya Sandra; Angela Nurini Agni; Suhardjo Suhardjo; Retno Ekantini; Muhammad Bayu Sasongko (Majalah Oftalmologi Indonesia, 2023)
Introduction dan Aim: Diabetic Macular Edema (DME) in Diabetic Retinopathy (DR) patients might threaten the patient's visual acuity. Therefore, a robust DME treatment is needed to prevent sight threatening condition in DR patients. In this study, we intended to compare the effects of intravitreal administration of bevacizumab versus bevacizumab and topical natrium diclofenac in DR patients who developed DME. Methods: This was a randomized controlled trial study with double blinds. Data were taken from April 2020 to June 2021 from the Dr. Sardjito Central General Hospital and the Dr. Suhardi Hardjolukito Indonesian Air Force Central Hospital, Yogyakarta. Our patients were assigned to a control group (intravitreal bevacizumab therapy only) and an intervention group (intravitreal bevacizumab and topical natrium diclofenac). Then, we evaluated best corrected visual acuity (LogMar) and intraocular pressure (IOP, mmHg) were recorded in both groups before and after therapy. Results: A total of 38 eyes from 36 patients with naive DME were included in this study. Both treatment groups showed a statistically significant improvement in visual acuity after treatment bevacizumab (pre = 0.8±0.5; post = 0.6±0.5; p-value = 0.033) and bevacizumab and natrium diclofenac (pre = 0.9±0.5; post = 0.5±0.3; p-value = 0.004). In contrast to the above findings, the IOP in both groups did not show a significant change in IOP after therapy, bevacizumab (pre = 15.7±4.1; post = 15.6±4.2; p-value = 0.810) and bevacizumab and natrium diclofenac (pre = 16.0±4.5; post = 16.0±3.9; p-value = 0.868). Conclusion: Our study showed that visual acuity was improved significantly in DME patients treated with either bevacizumab or bevacizumab and natrium diclofenac. This might be a valuable information on the improvement of DME therapy, given that no increased post-therapy IOP in patients treated topical natrium diclofenac.